2021
DOI: 10.1016/j.heliyon.2021.e06448
|View full text |Cite
|
Sign up to set email alerts
|

Career choices of Pharmacy and Pharm D undergraduates: attitudes and preferences

Abstract: Background The remarkably increasing number of graduated pharmacists necessitates exploring the current Pharmacy and Pharm D students’ future career choices in order to help the health policy makers to enhance effective health and education workforce planning. Objective To identify Pharmacy and Pharm D undergraduates’ attitudes and preferences toward different career choices and the factors that influence their career choice. Methods Across s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 17 publications
3
10
1
Order By: Relevance
“…The study revealed that medical sales representative was an undesirable career domain, as it was chosen by only 3.2% of respondents. This finding contradicts the studies conducted in Jordan and Iraq [14,29], in which participants ranked medical representatives among the top-three preferred future career domains. Globally, most pharmaceutical companies allocate a relatively high budget for employing and training medical representatives; pharmaceutical product promotion and marketing expenditure is higher than research and development expenditure [33].…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…The study revealed that medical sales representative was an undesirable career domain, as it was chosen by only 3.2% of respondents. This finding contradicts the studies conducted in Jordan and Iraq [14,29], in which participants ranked medical representatives among the top-three preferred future career domains. Globally, most pharmaceutical companies allocate a relatively high budget for employing and training medical representatives; pharmaceutical product promotion and marketing expenditure is higher than research and development expenditure [33].…”
Section: Discussioncontrasting
confidence: 93%
“…Results of this study highlighted the high female-to-male ratio (86%:14%). This finding is similar to those in many studies conducted among pharmacy students in Jordan [8,14]. Saudi Arabia [15], and Malaysia [16,17].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to what was reported in the literature, pharmacy was not always the first choice for studying for pharmacy students [ 13 16 ]. However, unlike previous studies, in this study, the majority, almost 70%, reported that pharmacy was their preferred field of study.…”
Section: Discussionsupporting
confidence: 62%
“…Based on the literature review and confirming competencies through the Delphi method, the findings indicate that digital skills are the most prioritized skill. The capabilities involve a basic ability to process information and communication technology (ICT) ( Jarab et al., 2021 ; Wuri Handayani et al., 2018 ). ICT is at the core of rapid change in the economy and is the foundation for innovation.…”
Section: Discussionmentioning
confidence: 99%